Effects of graphene oxide on the performance, microbial community dynamics and antibiotic resistance genes reduction during anaerobic digestion of swine manure. (December 2017) - Zhang, Junya; Wang, Ziyue; Wang, Yawei; Zhong, Hui; Sui, Qianwen; Zhang, Changping; Wei, Yuansong
Highlights: GO addition negatively influenced the methane production from swine manure. GO had little influence on the changes of microbial community. ARGs reduction was realized mainly at the acetogenesis and methanogenesis phase. Balance between the ARGs proliferation and ARGs destruction by GO existed. MRGs contributed most to the ARGs variation directly. Abstract: The role of graphene oxide (GO) on anaerobic digestion (AD) of swine manure concerning the performance, microbial community and antibiotic resistance genes (ARGs) reduction was investigated. Results showed that methane production was reduced by 13.1%, 10.6%, 2.7% and 17.1% at GO concentration of 5 mg/L, 50 mg/L, 100 mg/L and 500 mg/L, respectively, but propionate degradation was enhanced along with GO addition. Both bacterial and archaeal community changed little after GO addition. AD could well reduce ARGs abundance, but it was deteriorated at the GO concentration of 50 mg/L and 100 mg/L and enhanced at 500 mg/L, while no obvious changes at 5 mg/L. Network and SEM analysis indicated that changes of each ARG was closely associated with variation of microbial community composition, environmental variables contributed most to the dynamics of ARGs indirectly, GO influenced the ARGs dynamics negatively and (heavy metal resistance genes (MRGs)) influenced the most directly.